Accuracy and reliability of a method for measuring three-dimensional articular motions of the shoulder complex during swimming - Du, T.; Yanai, T. (Sports Biomechanics, 2022)
This technical report introduces a method for measuring the three-dimensional articular motions of the shoulder complex during swimming. Eleven collegiate swimmers performed front-crawl strokes at maximal effort and their shoulder motions were measured with an electromagnetic tracking device. Sensors were attached to the sternum, acromia and humeri to determine their relative positions and orientations. A cart carrying the components of the device was pushed back-and-forth along the poolside, so that the sensors attached to the swimmer could be detected within the electromagnetic field. The stroke-to-stroke reliability of the measured articular motions was determined for each swimmer. The accuracy of the device was tested by measuring the relative positions and orientations of multiple sensors fixed on a wooden stick moving above and below the water surface. The measured values were compared with pre-determined fixed values. The coefficient of variance for the joint angles between stroke cycles was <10% of the total range of movement. Within a range of 1282 mm from the transmitter, the root-mean-square error of measurement was 0.7° for orientation and 4 mm for position, both of which were superior to optical measurements. This method is accurate and reliable for measuring the kinematics of the shoulder complex during swimming.